2020
DOI: 10.1002/anie.202000678
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Flow Synthesis of ZIF‐8 Biocomposites with Tunable Particle Size

Abstract: Zeolitic imidazolate framework (ZIF) biocomposites show the capacity to protect and deliver biotherapeutics. To date, the progress in this research area is based on laboratory batch methods. Now, the first continuous flow synthetic method is presented for the encapsulation of a model protein (bovine serum albumin, BSA) and a clinical therapeutic (α1‐antitrypsin, AAT) in ZIF‐8. The in situ kinetics of nucleation, growth, and crystallization of BSA@ZIF‐8 were studied by small‐angle X‐ray scattering. By controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 59 publications
(65 reference statements)
1
48
0
Order By: Relevance
“…Kinetics of nucleation, particle growth, 38 crystallization, and the morphology of the particles were investigated in situ via synchrotron-based small-angle and wide-angle X-ray scattering (SAXS/WAXS) techniques. 42,43 We investigated four different samples (20×16 Lp@ZIF, 20×16 ZIF-L, 40×16 Lp@ZIF, and 40×16 ZIF-L) using a stopped flow device to initiate the rapid mixing of the reagents (mixing time <100 ms). See the SAXS section of the SI for full experimental details.…”
Section: Mechanism Of Zif Growthmentioning
confidence: 99%
“…Kinetics of nucleation, particle growth, 38 crystallization, and the morphology of the particles were investigated in situ via synchrotron-based small-angle and wide-angle X-ray scattering (SAXS/WAXS) techniques. 42,43 We investigated four different samples (20×16 Lp@ZIF, 20×16 ZIF-L, 40×16 Lp@ZIF, and 40×16 ZIF-L) using a stopped flow device to initiate the rapid mixing of the reagents (mixing time <100 ms). See the SAXS section of the SI for full experimental details.…”
Section: Mechanism Of Zif Growthmentioning
confidence: 99%
“…For example, microfluidics-assisted encapsulation was proposed to synthesize nanoZIF-8 biocomposites that are suitable for intracellular delivery. [26] Qu et al have developed an erythrocyte membranecloaked MOF-based biomimetic nanoreactor encapsulating GOx and the prodrug tirapazamine (TPZ). [34] In vitro and in vivo outcomes indicated that this biomimetic nanoreactor could enter tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another report by Falcaro's group was indicated that continuous flow synthesis of proteins@ZIF-8 biocomposites in a microfluidic setup enable to controlled the particle size of proteins@ZIF-8 in the 40 to 100 nm range. [26] This microfluidicassisted encapsulation method was then applied to the synthesis of α1-antitrypsin@ZIF-8 biocomposite with the size suitable for intravenous drug delivery applications.…”
Section: In Situ Encapsulationmentioning
confidence: 99%
“…Defects are deviations from the periodic structure in the crystal. The destruction of the crystal structure will lead to new properties of the electronic structure, which is different from that in the perfect crystals [30–33] . At the same time, the defects in crystals will also cause the redistribution of electron density, thereby increase the binding energy of metal oxides and metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of the crystal structure will lead to new properties of the electronic structure, which is different from that in the perfect crystals. [30][31][32][33] At the same time, the defects in crystals will also cause the redistribution of electron density, thereby increase the binding energy of metal oxides and metal atoms. Therefore, the defects in catalysts will tune the reaction surface/interface properties, the electronic structures, the reaction path and the free energy of reactant adsorption.…”
Section: Introductionmentioning
confidence: 99%